Traditional Market Resilience and Adaptation in Indonesia: A Systematic Literature Review from an Islamic Economics Perspective - Rifki Ramadhan; Ega Saputra; Rizal Fahlefi (Universitas Muhammadiyah Makassar, 2026)
Traditional markets have faced mounting competitive pressure from the rapid expansion of modern retail over the past two decades. This study analyzes the resilience of Indonesian traditional markets against modern-market dominance from an Islamic economics perspective, identifying the factors shaping their competitiveness and formulating adaptation strategies aligned with justice, sustainability, and the public good. Using a qualitative Systematic Literature Review under the PRISMA 2020 protocol, we synthesized 25 selected sources from 185 initial records retrieved from Google Scholar, Garuda Portal, DOAJ, and SINTA. Thematic analysis identified seven dominant themes social capital and communal trust, operational digitalization, regulation and legal protection, physical revitalization and management, local product differentiation, the Islamic economics perspective, and policy advocacy with social capital and digitalization confirmed as the two primary determinants of resilience. Islamic economic values, including honesty, the prohibition of gharar, economic ukhuwah, and the protection of small businesses, emerged as the ethical foundation of that resilience. The study’s principal contribution is a Six-Dimension Adaptation Strategy Model, grounded in Islamic economic values, that integrates the social, economic, institutional, digitalization, regulatory, and public-welfare dimensions traditional markets need to strengthen their resilience and compete with modern markets